Residual antibacterial effect of calcium hydroxide combined with chlorhexidine gel as an intracanal medicament - Nawal A Al-Sabawi; Fatima A Mohammad; Njwan F Shehab (Wolters Kluwer Medknow Publications, 2020)
Introduction: Bacterial elimination from the root canal system is considered as an essential factor for a successful endodontic treatment. Aims: To investigate both in vitro and in vivo efficacy of calcium hydroxide paste (CH) combined with 2% chlorhexidine gel (CHX) at various time intervals on Enterococcus faecalis (E.f) when used as an intracanal medicament (ICM). Materials and Methods: For the in vitro study, 45 single-rooted teeth were used. After instrumentation, roots were infected with E.f and then divided into three groups (gps) (15 n/gp) according to the time interval for the medicament to be left inside the canal (1 week, 2 weeks and 3 weeks). ICM used was 2% CHX combined with CH (CH + CHX). At the end of each time interval, the antibacterial effect was evaluated using the agar diffusion test. For the in vivo study, 45 single-rooted teeth were selected. After sterilisation and access opening, the first pre-treatment sample was taken, then after instrumentation second post-instrumentation sample was obtained. Later, teeth were divided into 3 gps (15 n/gp) (1 week, 2 weeks and 3 weeks) according to the time interval for the medicament to be left inside the canal. ICM used was 2% CH + CHX. After each period, the third post-medication sample was taken. ANOVA and Tukey post hoc tests were used for statistical analysis. Results: Both in vitro and in vivo studies have found that 2% of CH + CHX had a significant antibacterial effect for 1 week and 2 weeks. However, the antibacterial effect was significantly decreased after 3 weeks. Conclusions: CH + CHX can be used successfully for the reduction of E.f for 14 days when used as ICM.